The Ameliorative Effect of Mahuang Fuzi and Shenzhuo Decoction on Membranous Nephropathy of Rodent Model is Associated With Autophagy and Wnt/β-Catenin Pathway - Gao, Yu; Dai, Haoran; Zhang, Na; Jiang, Hanxue; Zhang, Zihan; Feng, Zhendong; Dong, Zhaocheng; Liu, Wenbin; Liu, Fei; Dong, Xuan; Zhao, Qihan; Zhou, Xiaoshan; et al. (Frontiers in Pharmacology, 2022)
The increased incidence of membranous nephropathy (MN) has made it the most common pathological type of primary nephrotic syndrome in adults in China. According to the theory of Traditional Chinese Medicine (TCM), Mahuang Fuzi (Chinese ephedra and Radix Aconiti Lateralis Preparata) and Shenzhuo Decoction (MFSD) could be used to treat such diseases. We treated patients of MN with MFSD, and observed comparable efficacy to glucocorticoid and/or immunosuppressants. In this study, we observed the therapeutic effect of MFSD on the rat model of passive Heymann nephritis (PHN), a classical MN model. Our results showed that MFSD treatment significantly reduced urinary protein level and podocyte injury in PHN rats, and correspondingly improved renal pathology, with the improvement effect on MN comparable to that of Cyclosporine A (CsA) alone. To explore the potential therapeutical mechanism of MFSD, the main chemical components of MFSD were determined by High-performance liquid chromatography-mass spectrometry (HPLC-MS). There were about 30 active components of MFSD. Next, based on network pharmacology methods, we screened related targets of MSFD on MN, which provided a preliminary understanding of the MFSD bioactive compounds. The clustering analysis showed that its active site might be in the autophagy-related protein and Wnt/β-catenin pathway, which was related to podocyte injury. Finally, we observed an improvement in renal autophagy and a down-regulation of the Wnt/β-catenin pathway after MSFD treatment in a PHN rat model. According to this study, autophagy and Wnt/β-catenin pathway may be potential targets for MFSD in the treatment of MN.